1980
DOI: 10.1093/ajcn/33.12.2613
|View full text |Cite
|
Sign up to set email alerts
|

Zinc status and its relation to growth retardation in children with chronic inflammatory bowel disease

Abstract: Zinc status was studied in 30 patients with chronic inflammatory bowel disease (CIBD) as well as in 17 normal children, 13 primordial short stature, and 17 anorexia nervosa patients. Basal serum and urinary excretion levels of zinc were measured in all patients. In addition, a zinc loading test was performed in 16 CIBD patients, 21 normal and/or short stature children, and nine patients with anorexia nervosa. Eleven of 30 patients with CIBD had serum zinc values less than 0.7 microgram/ml, whereas none of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Fasting plasma zinc was lower in the CD subjects than the controls, consistent with other studies in CD with (19) or without gut resection (6,8,14,16,17,42). It has been suggested that the lower plasma (or serum) zinc in CD might result from a lower serum albumin concentration (12,13).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Fasting plasma zinc was lower in the CD subjects than the controls, consistent with other studies in CD with (19) or without gut resection (6,8,14,16,17,42). It has been suggested that the lower plasma (or serum) zinc in CD might result from a lower serum albumin concentration (12,13).…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have suggested that urinary zinc excretion is lower in CD patients (17,(42)(43)(44), presumably as an adaptation to suboptimal zinc status. In our study, urinary zinc excretion was similar in the CD subjects and the controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Juvenile-onset Crohn's disease reportedly causes marked growth retardation or results in the delay of secondary sexual maturation (5, 6), whereas colitis ulcerosa, also a nonspecific inflammatory disease, rarely is accompanied by severe growth retardation. Growth retardation associated with chronic inflammatory bowel disease is probably caused by malnutrition (2,7,8), endocrine abnormalities (9, 10), use of steroid hormones (1 1) and deficiency of trace elements, such as zinc (12). Some reports contradict the theory that endocrine function related to GHsecretion is impaired in the presence of Crohn's disease; normal GHsecretion has been reported in Crohn's disease patients (13,14).…”
Section: Discussionmentioning
confidence: 99%